International validation of the European Organisation for Research and Treatment of Cancer QLQ‐BRECON23 quality‐of‐life questionnaire for women undergoing breast reconstruction. Issue 3 (8th November 2017) - Winters, Z. E.; Afzal, M.; Rutherford, C.; Holzner, B.; Rumpold, G.; da Costa Vieira, R. A.; Hartup, S.; Flitcroft, K.; Bjelic‐Radisic, V.; Oberguggenberger, A.; Panouilleres, M.; Mani, M.; et al.
Abstract : Background: The aim was to carry out phase 4 international field‐testing of the European Organisation for Research and Treatment of Cancer (EORTC) breast reconstruction (BRECON) module. The primary objective was finalization of its scale structure. Secondary objectives were evaluation of its reliability, validity, responsiveness, acceptability and interpretability in patients with breast cancer undergoing mastectomy and reconstruction. Methods: The EORTC module development guidelines were followed. Patients were recruited from 28 centres in seven countries. A prospective cohort completed the QLQ‐BRECON15 before mastectomy and the QLQ‐BRECON24 at 4–8 months after reconstruction. The cross‐sectional cohort completed the QLQ‐BRECON24 at 1–5 years after reconstruction, and repeated this 2–8 weeks later (test–retest reliability). All participants completed debriefing questionnaires. Results: A total of 438 patients were recruited, 234 in the prospective cohort and 204 in the cross‐sectional cohort. A total of 414 reconstructions were immediate, with a comparable number of implants (176) and donor‐site flaps (166). Control groups comprised patients who underwent two‐stage implant procedures (72, 75 per cent) or delayed reconstruction (24, 25 per cent). Psychometric scale validity was supported by moderate to high item‐own scale and item‐total correlations (over 0·5). Questionnaire validity was confirmed by good scale‐to‐sample targeting, and computable scale scores exceeding 50 per cent, except nipple cosmesis (over 40 per cent). In known‐group comparisons, QLQ‐BRECON24 scales and items differentiated between patient groups defined by clinical criteria, such as type and timing of reconstruction, postmastectomy radiotherapy and surgical complications, with moderate effect sizes. Prospectively, sexuality and surgical side‐effects scales showed significant responsiveness over time ( P < 0·001). Scale reliability was supported by high Cronbach's α coefficients (over 0·7) and test–retest (intraclass correlation more than 0·8). One item (finding a well fitting bra) was excluded based on high floor/ceiling effects, poor test–retest and weak correlations in factor analysis (below 0·3), thus generating the QLQ‐BRECON23 questionnaire. Conclusion: The QLQ‐BRECON23 is an internationally validated tool to be used alongside the EORTC QLQ‐C30 (cancer) and QLQ‐BR23 (breast cancer) questionnaires for evaluating quality of life and satisfaction after breast reconstruction. Abstract : Useful tool